Phenytoin-Associated Granulomatous Pulmonary Vasculitis. (January 2016) - Kheir, Fayez; Daroca, Philip; Lasky, Joseph
Abstract : Phenytoin was introduced in 1938 for the control of seizure disorders and remains widely used today. Since that time, many cases of phenytoin-induced allergic reactions and clinical pulmonary disease have been reported. However, pulmonary vascular pathology from phenytoin use has been only very rarely described. We report a case of phenytoin-associated vasculitis in a 39-year-old African American man presenting with progressive dyspnea and abnormal chest imaging. The importance of reviewing the medication history along with familiarity with the array of drug-associated lung diseases is crucial to recognize and treat pneumotoxicity.